2021
DOI: 10.1155/2021/6669263
|View full text |Cite
|
Sign up to set email alerts
|

Production of Biosurfactants by Ascomycetes

Abstract: Surfactants are utilized to reduce surface tension in aqueous and nonaqueous systems. Currently, most synthetic surfactants are derived from petroleum. However, these surfactants are usually highly toxic and are poorly degraded by microorganisms. To overcome these problems associated with synthetic surfactants, the production of microbial surfactants (called biosurfactants) has been studied in recent years. Most studies investigating the production of biosurfactants have been associated mainly with bacteria an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…and Fusarium sp. have the ability to produce biosurfactants with wide range variety and spectrum (Santhappan and Pandian 2017;Reis et al 2018;Sanches et al 2021). According to available published articles, the current study is the rst study to prove the ability of Aspergillus wentii to produce biosurfactant.…”
Section: Biosurfactant Production Determinationmentioning
confidence: 94%
See 1 more Smart Citation
“…and Fusarium sp. have the ability to produce biosurfactants with wide range variety and spectrum (Santhappan and Pandian 2017;Reis et al 2018;Sanches et al 2021). According to available published articles, the current study is the rst study to prove the ability of Aspergillus wentii to produce biosurfactant.…”
Section: Biosurfactant Production Determinationmentioning
confidence: 94%
“…Bacteria, especially the genus Pseudomonas, play a major role in production of biosurfactants (Nadella et al 2018). Moreover, many studies have reported the ability of different types of fungal species to produce biosurfactants such as sophorolipids produced by Candida bombicola, lipid carbohydrate protein based bioemulsi ers produced by Yarrowia lipolytica (Casas and Garcia-Ochoa 1999), monoketide and polyketide derivatives produced by Penicillium chrysogenum (Sanches et al 2021), spiculisporic acid produced by Penicillium spiculisporum (Ban and Sato 1993), cellobiose lipids produced by Ustilago maydis (Teichmann et al 2007), and chromone derivative produced by Aspergillus versicolor (Lin et al 2003). The main aim of the present study is to investigate the production of biosurfactants from soil fungal isolates and to study the effect of sun ower oil, olive oil, corn oil, and waste frying oil on the production of these biosurfactants.…”
Section: Introductionmentioning
confidence: 99%
“…Given the advances in renewable solutions and the implementation of regulatory requirements for environmental safety, there is a growing demand for bio-based surfactants [64]. Studies have shown that most biosurfactant industries are based in Europe, Asia and North America, with Europe as the market leader controlling about 52.5% of the global share in 2019 [36]. This was largely attributed to heightened consumer awareness concerning the negative impacts of chemical surfactants in these climes [36].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Synthetic and chemical surfactants are produced from petrochemicals and are increasingly used, even though they may have an impact on the environment and human health. Hence, there is a need to develop alternative molecules such as biosurfactants [3].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a quite large number of studies have highlighted biosurfactant production in yeasts and filamentous fungi, mostly belonging to the Ascomycota phylum, e.g., Aspergillus, Candida, Fusarium, and Penicillium spp. [3]. Sophorolipids, which are notably produced by the yeast Starmerella bombicola (syn.…”
Section: Introductionmentioning
confidence: 99%